Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Anugrah Analisis Sempurna Di Kota Depok - Mohammad Faiz Irawan; Endang Suprapti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the influence of work discipline and work motivation on employee performance at PT Anugrah Analisis Sempurna in Depok City, both partially and simultaneously. The research method used is a quantitative method with an associative approach. The sampling technique employed is saturated sampling, whereby all employees totaling 60 individuals were included as research samples. Data analysis techniques consisted of instrument testing, classical assumption testing, quantitative analysis, and hypothesis testing. The results of the study indicate that based on the t-test, the work discipline variable (X1) has a significant effect on employee performance (Y), as evidenced by the value of t count > t table (6.799 > 1.671). Thus, H0 is rejected and H1 is accepted, meaning that work discipline significantly influences employee performance. The multiple linear regression equation obtained is Y = 4.544 + 0.933X2. The correlation coefficient of 0.641 indicates a strong relationship, while the coefficient of determination of 64.1% shows that work discipline and work motivation collectively explain 64.1% of the variation in employee performance. Simultaneously, work discipline and work motivation are proven to have a positive and significant effect on employee performance. This is supported by the F-test results showing that F count > F table (115.417 > 3.159) with a significance value of 0.000 < 0.05. Therefore, H0 is rejected and H3 is accepted, meaning that there is a positive and significant influence of work discipline and work motivation on employee performance simultaneously at PT Anugrah Analisis Sempurna in Depok City.